Resisting disaster chronopolitics: Favelas and forced displacement in Rio de Janeiro, Brazil. (September 2021) - Barbosa, Luciana Mendes; Coates, Robert
Abstract: This article employs the notion of chronopolitics (Klinke 2013 [1]) to explore the place of disaster events within urban politics. A chronopolitics of disaster focuses on both governmental manipulation of the post-disaster space and the use of memory in resisting longstanding patterns of urban spatial segregation and forced removal: the creation and embodiment of alternative narratives of time and space to those mobilized by hegemonic actors. We draw here on the aftermath of calamitous landslides in favelas in Rio de Janeiro in 2010, during which 67 people died. In the wake of this traumatic event, the state moved quickly to close down political openings produced by the tragedy (Edkins 2006 [2]), focussing public attention on 'future risk' in order to put in place a rapid "recall" to favela displacement; a constant in Rio's politics since the early twentieth century. While changes in urban land formalisation and rights since the 1980s positioned forced displacement as an exception, we argue here that the much newer reductive vision of favelas as 'at-risk' places enables a return to the sovereign right to displace them. By working within a "time out of joint" (Zebrowski 2013: 213 [3]), the municipality established a dominant narration of city history that reinforces favelas as the principle problem facing urban politics, making displacement inevitable. The disaster event, then, elevates the politics of emergency response to a category of exceptionality in the post-dictatorship period, and lays the foundation for a renewed favela politics: a chronopolitics of disaster. The paper inductively expands the concept of chronopolitics, a politics of time, to analyse how calamitous events are used to normalise the exceptional, and how trauma and memory challenge narratives inspired by modern aspirations of a Rio without favelas.